Piezo-tolerant natural gas-producing microbes under accumulating pCO2. Issue 1 (December 2016) - Lindeboom, Ralph; Shin, Seung; Weijma, Jan; Lier, Jules; Plugge, Caroline
Abstract Background It is known that a part of natural gas is produced by biogenic degradation of organic matter, but the microbial pathways resulting in the formation of pressurized gas fields remain unknown. Autogeneration of biogas pressure of up to 20 bar has been shown to improve the quality of biogas to the level of biogenic natural gas as the fraction of CO2 decreased. Still, thep CO2 is higher compared to atmospheric digestion and this may affect the process in several ways. In this work, we investigated the effect of elevatedp CO2 of up to 0.5 MPa on Gibbs free energy, microbial community composition and substrate utilization kinetics in autogenerative high-pressure digestion. Results In this study, biogas pressure (up to 2.0 MPa) was batch-wise autogenerated for 268 days at 303 K in an 8-L bioreactor, resulting in a population dominated by archaealMethanosaeta concilii, Methanobacterium formicicum andMtb. beijingense and bacterialKosmotoga -like (31% of total bacterial species), Propioniferax -like (25%) andTreponema -like (12%) species. Related microorganisms have also been detected in gas, oil and abandoned coal-bed reservoirs, where elevated pressure prevails. After 107 days autogeneration of biogas pressure up to 0.50 MPa ofp CO2, propionate accumulated whilst CH4 formation declined. Alongside thePropioniferax -like organism, a putative propionate producer, increased in relative abundance in the period of propionate accumulation. Complementary experiments showed that specific propionate conversion rates decreased linearly from 30.3 mg g−1 VSadded day−1 by more than 90% to 2.2 mg g−1 VSadded day−1 after elevatingp CO2 from 0.10 to 0.50 MPa. Neither thermodynamic limitations, especially due to elevated pH2, nor pH inhibition could sufficiently explain this phenomenon. The reduced propionate conversion could therefore be attributed to reversible CO2 -toxicity. Conclusions The results of this study suggest a generic role of the detected bacterial and archaeal species in biogenic methane formation at elevated pressure. The propionate conversion rate and subsequent methane production rate were inhibited by up to 90% by the accumulatingp CO2 up to 0.5 MPa in the pressure reactor, which opens opportunities for steering carboxylate production using reversible CO2 -toxicity in mixed-culture microbial electrosynthesis and fermentation.Graphical abstract The role ofp CO2 in steering product formation in autogenerative high pressure digestion